DeRisking coffee in the Central Highlands: piloting a Coffee Climate Protection Insurance (CCPI) scheme for farmers and agribusinesses - Barlis, Angelica; Mushtaq, Shahbaz; Bossolasco, Laurent; Kath, Jarrod; Swaans, Cornelis P.M. (DeRISK SE Asia, 2022)
This brief provides an overview of the piloting of the Coffee Climate Protection Insurance (CCPI) scheme introduced and piloted in the Central Highlands of Vietnam together with ECOM Sustainability Management Services (SMS). Two index-insurance products were developed and piloted specifically for low rainfall/drought cover and excess rainfall for Lam Dong and Dak Lak provinces